Umbilical hernia in pediatric patients attending outpatient department in tertiary care centre - Sharma, Harsh Vardhan; Rasool, Ifra; Gupta, Ravinder K.; Afeeh, Ariba; Khajuria, Anmol (International Journal of Contemporary Pediatrics, 2024)
Background: Umbilical hernias are estimated to affect 15% of children. Age, race, gestational age, and coexisting disorders are some of the variables that affect it. In comparison to the general population, there are greater incidences of connective tissue illnesses in children, premature delivery, low birth weight, syndromic newborns, black children, and children with pathologies that raise intraabdominal pressure. To determine the prevalence and to assess the risk factors of umbilical hernia in pediatric patients attending outpatient department (OPD) in tertiary care centre. Methods: The present observational study was conducted in paediatric OPD, of a tertiary care centre over a period of one year. A total of 100 study subjects were enrolled with suspected umbilical hernia. The data was collected with the help of a structured clinical proforma and analysed with SPSS version 20.0. Results: In our study the most prevalent age group involved being 0-1 years (6%) followed by 8-10 years (3%) and 2-4 years (2%). Umbilical hernia was seen more in males (64%) than females. Low birth weight (81%), premature delivery (54.54%), and undernutrition (90.9%) were the risk factors that were observed to be associated with the development of umbilical hernia. Conclusions: The study concluded that the overall prevalence of umbilical hernia was 11% and the associated risk factors were premature delivery, low birth weight and poor nutrition.